Chemical synthesis of porous hierarchical Ge–Sn binary composites using metathesis reaction for rechargeable Li-ion batteries. Issue 96 (12th October 2015) - Lin, Ning; Zhou, Jie; Han, Ying; Zhang, Kailong; Zhu, Yongchun; Qian, Yitai
Abstract : A typical metathesis reaction is employed to prepare porous hierarchical Ge–Sn binary composites. As an anode for half/full LIBs, the Ge–Sn displays superior electrochemical performance. Abstract : Direct metathesis reaction between Mg2 Ge and SnCl4 is introduced to prepare porous hierarchical Ge–Sn binary composites, in which the Ge and Sn components are distributed uniformly, with a tap density of 2.3 g cm −3 . As an anode for LIBs, the Ge–Sn composite displays a specific capacity of 980 mA h g −1 at 0.5 A g −1 after 250 cycles, and 890 mA h g −1 at 3 A g −1 over 1700 cycles. When paired with a commercial LiCoO2 cathode, a 3.6 V full battery with a capacity of 830 mA h g −1 is obtained.